Significance of Economic Activities in Environmental Protection: Evidence from a Panel of 4-ASEAN Economies - Tirtayasa, Satria; Akrim, A.; Gunawan, Ade; Sulasmi, Emilda; Anisah, Hastin Umi (International Journal of Energy Economics and Policy, 2021)
Environmental degradation is increasing gradually due to economic activities by the Association of Southeast Asian Nations (ASEAN). ASEAN energy center estimated 4.4 percent increase in the consumption of final energy among ASEAN nations in 2030 which is greater than the average growth rate of 1.44%. The current study empirically analyzes the impact of economic activities on environmental protection across four largest ASEAN economies (Indonesia, Thailand, Singapore and Malaysia) over a period of 1998-2018. In order to achieve this objective, the study employs several panel econometric tests; ADF, panel cross-sectional dependence, Johansen-Fisher panel cointegration, FMOLS and country specific long run output method.” The study finds significant positive impact of non-renewable energy consumption (NRNC), GDP and labor force on CO2 emission. Renewable energy consumption (RNC) has negative impact on CO2 emission. As RNC causes reducing CO2 emission in the sample ASEAN economies, the study suggests the policy makers to inductee effective policies to encourage the generation of renewable energy and its uses across ASEAN economies. While the generation of non-renewable energy should be discouraged as it promotes CO2 emission. Keywords: Economic Activities, Energy Consumption, GDP, ASEAN, FMOLS. JEL Classifications: R11, K32 DOI: https://doi.org/10.32479/ijeep.10831